Testing the efficiency of the wine market using unit root tests with sharp and smooth breaks - Elie Bouri; Tsangyao Chang; Rangan Gupta (Wine Economics and Policy, 2017)
This paper examines the efficient market hypothesis for the wine market using a novel unit root test while accounting for sharp shifts and smooth breaks in the monthly data. We find evidence of structural shifts and nonlinearity in the wine indices. Contrary to the results from conventional linear unit root tests, when we account for sharp shifts and smooth breaks, the unit root null for each of the wine indices has been rejected. Overall, our results suggest that the wine market is inefficient when we incorporate breaks. We provide some practical and policy implications of our findings. Keywords: Wine market, Efficiency, Sharp and smooth breaks, Unit root tests